Organic acid-ammonia ion-induced nucleation pathways unveiled by quantum chemical calculation and kinetics modeling: A case study of 3-methyl-1, 2, 3-butanetricarboxylic acid. (December 2021) - Xia, Deming; Chen, Jingwen; Wang, Ya; Xu, Tong; Su, Lihao; Xie, Hong-bin; Allen, David T.
Abstract: Nucleation of organic acids (OAs) and H2 SO4 is an important source for new particle formation in the atmosphere. However, it is still unclear whether organic acids can produce nanoparticles independent of H2 SO4 . In this study, 3-methyl-1, 2, 3-butanetricarboxylic acid (MBTCA) was adopted as a model of OAs. Pathways of clustering from MBTCA, ammonia and ions (NH4 + and NO3 − ) to form a 1.9 nm nucleus were investigated by quantum chemical calculation and kinetic modeling. Results show recombination of charged clusters/ions plays an essential role in the nucleation processes. Cluster formation rates increase by a factor of 10 3 when NH3 increases from 2.6 × 10 8 molecules·cm −3 (under clean conditions) to 2.6 × 10 11 molecules·cm −3 (under polluted conditions), as NH3 can stabilize MBTCA clusters and change ion compositions from H3 O + to NH4 + . Although the proposed new mechanism cannot compete with H2 SO4 –NH3 –H2 O or H2 SO4 -OA nucleation currently, it may be important in the future with the decline of SO2 concentration. Highlights: Nucleation pathways from organic acids, ammonia, and ions (NH4 + and NO3 − ) were identified. Ion-ion recombination were found to play an essential role in the nucleation processes. NH3 concentration can significantly increase cluster formation rates from organic acids, NH3, and ions.